Design And Simulation Of Lte Radio System For Broadband Wireless Access In Central Phnom Penh - Siren Seven; Rina Pudji Astuti; Budi Prasetya (eProceedings of Engineering, 2015)
Abstract—The huge number of users and new applications need higher access speeds and lower latency of wireless communication. As a result, operators need more capacity and higher efficiency to serve their costumer. LTE is designed to have wider channels up to 20MHz, with low latency and packet optimized radio access technology. The peak data rate envisaged for LTE is 100 Mbps in downlink and 50 Mbps in the uplink. In order to support the simultaneous use of legacy and new systems, the operator need to provide a better radio system, especially in central Phnom Penh. The aim of this study is to designs, simulates, analyzes and expose the state of the art of map planning LTE radio system. Special emphasis is laid on radio link budget along with detailed coverage area and capacity. The results cover the interference limited coverage calculation, the traffic capacity calculation and radio frequency assignment. The implementation is achieved on the software platform for the LTE Radio Planning and also can see the simulation antenna in Google Earth. The study will present a detailed LTE radio dimensioning procedure such as coverage area and capacity in Phnom Penh city. The simulation and analysis of the coverage by signal level and overlapping zone also a part of this work. Keywords— Long Term Evolution; MIMO; Coverage area; Capacity; Cost 231-Hata.